Energy Efficieny of Electric Knapsack Type Sprayer Powered by Solar Panel 20 WP - Falefi, Rifai; Mairizwan, M; Yulkifli, Y (PILLAR OF PHYSICS, 2024)
Indonesia, as an agricultural country that relies on the agricultural sector as a source of livelihood, is increasingly providing quality human resources to encourage progress in the agricultural sector. In an effort to advance the agricultural sector, various aspects need to be improved, one of which is the quality of even spraying of plant seeds. Therefore, the development of sprayers is a very relevant innovation. A sprayer is used by farmers to control pests and plant diseases. A sprayer is one of the agricultural equipment used by farmers to spray pesticides on plants to eradicate pests. The development of solar-powered sprayers has an impact on the environment and is a substitute for renewable energy. Then a test was carried out between the power produced by the solar panels and the power used by the pump. The first measurement was carried out and produced power on the solar panels with a total power of 1874.27 watts. The power used in the pump DC is 882.54 watts. Based on the power produced by the panel and the output of the sprayer, with a 20 wp solar panel in sunny conditions, you do not need a battery to drive the sprayer, but a battery is needed when the weather conditions are cloudy